Clustering Kabupaten/Kota di Jawa Tengah Tahun 2022 berdasarkan Jumlah Kasus Kemunculan Penyakit dengan Algoritma K-Means - Mufid, Nadiya Azhar; Hanum, Derra Risqi Nurulita; Sidiq, Aldy Hasbiya (Indonesian Journal Publisher, 2023)
This research aims to conduct clustering or grouping of Regencies/Cities in Central Java Province based on the number of occurrences of specific diseases in 2022 using the K-Means algorithm. The research results obtained 3 clusters, namely high, medium, and low for 29 Regencies and 6 Cities. The percentage for cluster 1 is 34.29%, consisting of 10 regencies and 2 cities, cluster 2 is 40.00%, consisting of 11 regencies and 3 cities, and cluster 3 is 25.71%, consisting of 8 regencies and 1 city. These clustering results can be used as a basis for making effective strategic decisions in the development of prevention and control efforts for diseases in each region.